Pre-service English teachers' practices of designing and implementing lesson plans for teaching practicum - Lestari, Anes Eka; Lestari, Sri (LingTera, 2022)
It is consequential for pre-service English teachers to be able to construct lesson plans as well as to implement those plans in the classroom. Such skills will help them teach more effectively when they become English teachers in the future. This study aims to investigate pre-service English teachers' practices in developing lesson plans for their teaching practicum during the pandemic. Employing a qualitative approach, the data were collected from document analyses and interviews involving students majoring in English Education who had completed their teaching practicum at a private junior high school. The findings revealed that the implemented activities in the English teaching practicum were mostly consistent with the lesson plans. This study also found that, despite the general consistency, the pre-service English teachers struggled to develop their lesson plans as they had to adjust the number of activities with the reduced time allotment due to the pandemic. In conclusion, the pre-service English teachers in this study were able to create lesson plans adapting to the limited duration of the English sessions for the practicum during the pandemic, but they were still unable to implement all the activities written on the plans due to the constraints of time and classroom management skills.